Vitamin C and E combination modulates oxidative stress induced by X-ray in blood of smoker and nonsmoker radiology technicians - Kayan, Mustafa; Nazıroğlu, Mustafa; Çelik, Ömer; Yalman, Kadir; Köylü, Halis (Cell biochemistry and function, 2009)
X‐ray radiation is detrimental to human cells and may lead to development of life‐threatening diseases. Cigarette smoke contains about 500 chemicals that include organic and oxidant compounds whereas vitamin C and E (VCE) have scavenger effects on the compounds. We investigated effects of VCE administration on X‐ray‐induced oxidative toxicity in blood of smoker and nonsmoker X‐ray technicians. Twenty technicians and 30 healthy age‐matched subjects control were used in the study. Ten of the X‐ray technicians and 15 of the control were smokers. Blood samples were taken from the control. Oral vitamin C (500 mg) and vitamin E (150 mg) were daily supplemented to the smoker and nonsmoker X‐ray technicians for 5 weeks. Blood samples were taken from the X‐ray technicians after and before 5 weeks. Plasma and erythrocytes lipid peroxidation (LP), reduced glutathione (GSH) levels, erythrocytes glutathione peroxidase (GSH‐Px), and plasma antioxidant vitamin concentrations were investigated in control and X‐ray technicians with smoker and nonsmoker. Plasma and erythrocytes LP levels were higher in the total X‐ray group and smoker X‐ray group than in control and nonsmoker X‐ray group, respectively although the LP level was decreased by the VCE treatment. The plasma vitamin C, vitamin A, vitamin E, and β‐carotene concentrations were lower in the X‐ray group than in control although their concentrations were increased by the treatment. The erythrocytes GSH level and GSH‐Px activity were found to be higher in the treatment group than in the X‐ray group. Plasma GSH level was not found to be different in all group. Reactive oxygen species may play role in the mechanism that has been proposed to explain the biological side effect of X‐ray radiation and smoke. VCE prevents the smoke and X‐ray‐induced oxidative stress to strengthen antioxidant vitamin concentrations in the blood of the technicians. Copyright © 2009 John Wiley & Sons, Ltd.